2012
DOI: 10.1523/jneurosci.4303-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Self-Renewal and Differentiation of Reactive Astrocyte-Derived Neural Stem/Progenitor Cells Isolated from the Cortical Peri-Infarct Area after Stroke

Abstract: In response to stroke, subpopulations of cortical reactive astrocytes proliferate and express proteins commonly associated with neural stem/progenitor cells, such as Glial Fibrillary Acidic Protein (GFAP) and Nestin. To examine the stem cell-related properties of cortical reactive astrocytes after injury, we generated GFAP-CreER™;tdRFP mice to permanently label reactive astrocytes. We isolated cells from the cortical peri-infarct area 3 days after stroke, and cultured them in neural stem cell medium containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 58 publications
4
172
1
Order By: Relevance
“…3). As mentioned, the similarities between parenchymal astrocytes and neural stem cells even extend to an intrinsic capacity of parenchymal astrocytes to generate neurons, at least when it comes to striatal astrocytes in vivo (Magnusson et al, 2014;Nato et al, 2015;Duan et al, 2015;Luzzati et al, 2014) and cortical astrocytes when isolated and cultured in vitro (Buffo et al, 2008;Shimada et al, 2012;Sirko et al, 2013). But the relatedness between the two cell types might go even further than that.…”
Section: Regional Differences In the Astrocyte Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…3). As mentioned, the similarities between parenchymal astrocytes and neural stem cells even extend to an intrinsic capacity of parenchymal astrocytes to generate neurons, at least when it comes to striatal astrocytes in vivo (Magnusson et al, 2014;Nato et al, 2015;Duan et al, 2015;Luzzati et al, 2014) and cortical astrocytes when isolated and cultured in vitro (Buffo et al, 2008;Shimada et al, 2012;Sirko et al, 2013). But the relatedness between the two cell types might go even further than that.…”
Section: Regional Differences In the Astrocyte Phenotypementioning
confidence: 99%
“…There are cells in the neocortex, including astrocytes, with an intrinsic capacity to generate neurons. This has been demonstrated by the fact that such cells can be isolated from the injured (Buffo et al, 2008;Sirko et al, 2013;Shimada et al, 2012) or even the healthy neocortex of rodents (Palmer et al, 1999;Grande et al, 2013;Sirko et al, 2013) and coaxed into producing neurons in vitro. But this, on its own, does not constitute adult neurogenesis.…”
Section: Neocortexmentioning
confidence: 99%
See 1 more Smart Citation
“…We isolated reactive astrocytes from peri-infarct tissues by magnetic-activated cell sorting (MACS) with antibodies against glutamate aspartate transporter-1 (GLAST) (20). At 3 d after stroke, FACS phenotyping of GLAST + reactive astrocytes from cortical tissues of C57BL/6J mice demonstrated that cellsurface Jagged1 expression was markedly up-regulated on cells from the ischemic ipsilateral side of the brain compared with cells from the contralateral side ( Fig.…”
Section: /Rc2mentioning
confidence: 99%
“…Although there is a conventional method for isolating and culturing astrocytes from neonatal mice, primary adult cortical reactive astrocytes survive poorly in culture. We recently reported the isolation and expansion of self-renewing, multipotent reactive astrocyte-derived neural stem cells (Rad-NSCs) derived from the cortical peri-infarct area after stroke (20). To avoid possible differences between neonatal and adult astrocytes, we developed methods to study signaling in adult astrocytes based on redifferentiated Rad-NSCs.…”
Section: /Rc2mentioning
confidence: 99%